A giant lacustrine flood‐related turbidite system in the Triassic Ordos Basin, China: Sedimentary processes and depositional architecture. Issue 7 (26th June 2021) - Chen, Peng; Xian, Benzhong; Li, Meijun; Liang, Xiaowei; Wu, Qianran; Zhang, Wenmiao; Wang, Junhui; Wang, Zhen; Liu, Jianping
Abstract: Turbidites have been regarded as an important sedimentary infilling component in both oceans and lakes, but limited studies have been performed on the mechanisms governing the initiation and development of lacustrine turbidite systems. The present study offers unique insight into the controls and potential extent of ancient lacustrine turbidite systems by an investigation of the Triassic Ordos Lake, where a large turbidite system had been traced across >25 653 km 2 . This article shows by comparison that the Triassic Ordos Lake turbidite system is larger than all known modern and ancient lacustrine counterparts. The exceptionally large intracontinental sag basin provided a relatively unconfined environment for the development of the turbidite system, explaining its vast extent. Extraordinary flood events formed during the Carnian Pluvial Episode facilitated continuous sediment supply into the turbidite system, supporting its accumulation. Lacustrine flood‐related turbidity currents travelled as sediment‐laden turbulent flows, showing an increase in the proportion of suspended‐load deposits and a decrease in the proportion of bed‐load deposits downstream from the river mouth. Five architectural elements have been revealed, reflecting a distinctive assemblage of erosional bedforms and depositional bedforms in channel‐lobe systems, and their recognition criteria were established. This study changes the traditional understanding of lacustrine turbidite systems, generally interpreted as having smaller sizes, and demonstrates likewise in the lacustrine realm, that extreme flood events can generate a world‐class deep‐water turbidite system, which can even be comparable with its submarine counterparts. This study also confirms that the combination of low‐gradient slopes and a long‐lived, mixed‐load, prograding fluvial feeder system can produce exceptionally large‐scale deep‐lake flood‐related turbidites. Furthermore, it has implications for the prediction of facies and reservoir quality in ancient lacustrine turbidite systems.